KAJIAN BIBLIOMETRIK PRODUK KOMBINASI HIDROGEL-OLEOGEL (BIGELS) - Febriansyah, Muhammad Irfan; Puteri, Nafisah Eka (Journal of Technology and Food Processing (JTFP), 2025)
Bigels, which are colloidal systems combining oleogel and hydrogel, demonstrate significant potential in the delivery and release of bioactive compounds, offering better physicochemical stability compared to emulsions and other gels. Bigels are capable of simultaneously transporting both lipophilic and hydrophilic components, making them ideal for applications in cosmetic, pharmaceutical, and food products. However, their development faces challenges such as the limited availability of safe oleogelators, the need to optimize rheological properties, and consumer acceptance. This study aims to conduct a bibliometric review to map the research trends on bigels, identify dominant topics, and analyze the latest developments in this field. Publication data was collected using the term "bigels" from Scopus and analyzed using Harzing’s Publish or Perish and VOSviewer. The results of the analysis revealed 156 publications related to bigels since 2008, with a total of 4,694 citations. Publication trends show a significant increase, with a focus on the use of bigels as fat replacers, active ingredient carriers, and in 3D printing technology. Dominant keywords include oleogel, hydrogel, emulgels, and their applications in pharmaceuticals and cosmetics. This study provides an overview of the direction of bigels research and their potential applications, although there are limitations regarding the scope of data, which is solely based on Scopus.